Candidates' Quality and Electoral Participation: Evidence from Italian Municipal Elections - Marco Alberto De Benedetto; Maria De Paola (Institute for the Study of Labor (IZA), 2014)
We analyze the impact of the quality of candidates running for a mayor position on turnout using a large data set on Italian municipal elections held from 1993 to 2011. We firstly estimate a municipal fixed effects model and show that an increase in the average quality of candidates competing at the electoral race produces a positive impact on turnout. To handle endogeneity issues arising from time variant unobservable features of electoral races, we build on the literature showing that politicians' quality is positively affected by their wage and apply a Fuzzy Regression Discontinuity Design relying on the fact that in Italy the wage of the mayor increases non-monotonically at different thresholds. Results show that an exogenous increase in the average quality of candidates, induced by a higher wage, leads to an increase in turnout by about 2 percentage points.
Keywords: D72; D78; J45; 330; politicians' quality; turnout; fuzzy regression discontinuity design; instrumental variables